Cascadic Multigrid for Parabolic Problems (Journal of Computational Mathematics, 2000)
In this paper, we develop the cascadic multigrid method for parabolic problems. The optimal convergence accuracy and computation complexity are obtained.
Keywords: Cascadic multigrid; Finite element; Parabolic problem.